Rancière and Emancipatory Art Pedagogies The Politics of Childhood Art - Park, Hayon (Bloomsbury Academic, 2022)
Draws on the philosophy of Jacques Rancière to reconsider approaches to childhood art education and offers a re-examination of the practices and pedagogies of childhood art.